MENGUNGKAP ANALISIS DAN EVALUASI KEBIJAKAN TENTANG PENDIDIKAN AGAMA DAN KEAGAMAAN - Benny Prasetiya (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
The implementation of PP No. 55/2007 is part of government intervention in religious and religious education. every policy stipulated in its implementation certainly raises constructive criticism. Criticism that arises starts from the aspects of laws and regulations, the implementation process and the impact of a policy in the set of approaches used in this research policy research that focuses on researching policy formulation. The content analysis technique in this research is to compare the contents/formulation of PP RI No. 55 of 2007 concerning Islamic religious education with public policy theory. The researcher selects the data source that has relevance to this policy study and concludes the data for conclusions. The results of the research found were the formulation of PP RI No. 55 of 2007 related to public policy objectives that are regulative, deregulation, dynamic or stabilizing. Regulatory aspects provide restrictions and regulate the implementation of Islamic religious education. The deregulation aspect has the purpose of liberating in terms of providing education. The aspects of dynamism as the driving force for national education goals. The purpose of stabilization is intended to make adjustments to the rules so that Islamic educational institutions follow the National Education Standards.